Disentangling the Simultaneous Effects of Inertial Losses and Fracture Dilation on Permeability of Pressurized Fractured Rocks - Jia‐Qing Zhou; Yi‐Feng Chen; Huiming Tang; Lichun Wang; M. Bayani Cardenas (Geophysical Research Letters, 2019)
Abstract How fluids flow through pressurized fractured rocks is relevant to many engineering applications and geophysical processes including fault rupturing, hydraulic fracturing, induced seismicity, fluid extraction, and contaminant transport. With increasing fluid pressure and concomitantly elevated hydraulic gradient, the permeability of fractured rock is reduced because of inertial losses within the fluid. There is an accompanying flow regime change when this happens. On the other hand, increasing pressure causes fracture dilation which enhances permeability. In this case, the fracture geometry changes. These two competing consequences of increasing pressure had always been studied independently. Here we present an analytical expression for fractured rock permeability where flow regime and medium geometry simultaneously co‐evolve. The theory was applied to core and field flow tests. With continuously increasing fluid pressure, the inertial effect on permeability first dominates over that of fracture dilation and this dominance theoretically reverses at Forchheimer number = 1/3.